Abstract: Death by compliance - The benefits of a risk-based approach to Health & Safety - Khyn, Agnès (New Zealand Journal of Health and Safety Practice, 2024)
Could we all say with the hand on our heart that we are doing everything ‘so far as is reasonably practicable’ to prevent injuries or incidents? This thought-provoking session will encourage a shift in mindset within health and safety practices. By emphasising the benefits of a risk-based approach over a compliance-focused one, it not only aims to enhance the performance and credibility of H&S professionals but also support Business Leaders to promote safer work environments and prevent injuries.